(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
This research aims to study some geotechnical properties of dunes in Shirqat district, northern Iraq, and the possibility of verifying their suitability for use as fine aggregate in concrete construction. Therefore, sampling is carried out from five different stations representing the sediments of the study area. The most important geotechnical properties of these sands have been investigated, including moisture content, specific gravity, and sieve analysis, in addition to conducting chemical tests (gypsum content, organic content, and total dissolved salts percentage). The results of the sieve analysis show that the sediments are coarse-type sand and are then classified as "poorly graded" according to the unified soil classification. The results show low soil moisture content values, and the aggregate is classified as an air-dry aggregate in terms of its content. Additionally, the values of the specific gravity of the soil vary slightly between 2.63 and 2.66. Conversely, there is an extensive variation in the gypsum content values from 2.14 to 14.68 percent, which could lead to thermal expansion and consequently weaken the concrete structure. In addition, the findings also reveal a large variation in the values of the organic matter content ranging between (3.81-16.05%), which may be due to the presence of organic impurities that negatively affect the durability of the concrete. Through the results of the sieve analysis of these dunes, it is found that the majority of the examined sediments do not conform to Iraqi Standard Specification No. 45 in 1984. Overall, the investigated sediments are not suitable for use in concrete construction.